1984
DOI: 10.1038/311656a0
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acids directly depolarize rat brain astrocytes in primary culture

Abstract: L-glutamic acid (L-Glu) and L-aspartic acid (L-Asp) are considered to be major excitatory amino acid transmitters, causing depolarization and excitation of neurones in the mammalian central nervous system (CNS). These responses have been thought to be an exclusively neuronal property as the excitatory amino acids either did not affect the potential of electrophysiologically unresponsive glial cells, or when an effect was seen, it was attributed to changes in external [K+] (refs 5, 6). Here we report that L-Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(159 citation statements)
references
References 20 publications
5
152
1
1
Order By: Relevance
“…In keeping with this, it has repeatedly been shown that astrocytes express a selection of glutamate receptors including kainate and AMPA receptors both of which are sensitive to kainate. 10,28,29 This was supported by several studies carried out in cultured astrocytes demonstrating alterations in cellular ion homeostasis after exposure to kainate including complex changes in intracellular concentrations of Na þ and H þ (see ref. 30) and increases in the extracellular K þ concentration likely due to increased astrocytic K þ efflux.…”
Section: Discussionmentioning
confidence: 66%
“…In keeping with this, it has repeatedly been shown that astrocytes express a selection of glutamate receptors including kainate and AMPA receptors both of which are sensitive to kainate. 10,28,29 This was supported by several studies carried out in cultured astrocytes demonstrating alterations in cellular ion homeostasis after exposure to kainate including complex changes in intracellular concentrations of Na þ and H þ (see ref. 30) and increases in the extracellular K þ concentration likely due to increased astrocytic K þ efflux.…”
Section: Discussionmentioning
confidence: 66%
“…Depolarization of the membrane above Ϫ75 mV should, therefore, lead to inward Na ϩ / HCO 3 Ϫ cotransport. K A depolarizes astrocytes by 5 mV/sec (Backus et al, 1989); the total depolarization can reach 20 -25 mV (Bowman and Kimelberg, 1984;Kettenmann and Schachner, 1985). The similar time courses of K A-induced alkalinization and depolarization (see Bowman and Kimelberg, 1984;Kettenmann and Schachner, 1985;Backus et al, 1989) strongly suggest that the alkalinization resulted from accelerated inward Na ϩ / HCO 3 Ϫ cotransport during K A application (see above).…”
Section: Origin Of K A-evoked [H ؉ ] I Changesmentioning
confidence: 63%
“…Likewise Glu-induced acidifications were resistant to CNQX (they actually increased), demonstrating that they too were not caused by ionotropic non-NMDA receptor activation. Glu transport is voltage dependent (Brew and Attwell, 1987), and if CNQX partially blocked the Glu-induced depolarization (Bowman and Kimelberg, 1984;Kettenmann and Schachner, 1985), Glu uptake and acidification would be increased. Reduction of Glu-induced depolarization also might have reduced a depolarization-dependent alkalinization process, thereby magnifying the acidification (see below).…”
Section: Origin Of Glu-and D-asp-evoked Acidificationsmentioning
confidence: 99%
“…The astrocytic Na + /K + -ATPase responds predominantly to increases in intracellular Na + concentration ([Na + ] i ) for which it shows a K m of about 10 mM (Kimelberg et al 1993). Since in cultured astrocytes, the N[Na + ] i ranges between 10 and 20 mM (Kimelberg et al 1993), Na + /K + -ATPase is set to be readily activated when N[Na + ] i rises concomitantly with glutamate uptake (Bowman & Kimelberg 1984). Indeed, recent evidence obtained in our laboratory using 86 Rb uptake to directly monitor the activity of the pump, shows that glutamate activates the Na + /K + -ATPase , 1997.…”
Section: Synaptically Released Glutamate Triggers Glucose Use In Astrmentioning
confidence: 99%